1992
DOI: 10.3109/10915819209141893
|View full text |Cite
|
Sign up to set email alerts
|

A Comprehensive, Integrated Review and Evaluation of the Scientific Evidence Relating to the Safety of the Herbicide 2,4-D

Abstract: The safety of 2,4-D to farm and forestry workers, commercial applicators and the general public has been of continuing concern because certain epidemiological studies of groups potentially exposed to 2,4-D have suggested a relationship between 2,4-D use and increased risk of soft tissue sarcoma, Hodgkin's disease or non-Hodgkin's lymphoma. This review on 2,4-D is unique in that the approach taken was to integrate data from worker exposure studies, whole animals, metabolic and other relevant laboratory studies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
94
0
3

Year Published

2001
2001
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 128 publications
(101 citation statements)
references
References 233 publications
3
94
0
3
Order By: Relevance
“…The toxicity of 2,4-D and other related compounds is attributed to the free acid form of the chemicals (Munro et al 1992) and may be mediated by effects associated with the plasma membrane, interference in cellular metabolic pathways involving acetyl coenzyme A, or uncoupling of oxidative phosphorylation (Bradberry et al 2000). Their herbicide action is mediated through plant hormone pathways, but to the best of our knowledge no solid evidence has been presented to date to support endocrine-like activity of these compounds in mammals or other species.…”
Section: Discussionmentioning
confidence: 99%
“…The toxicity of 2,4-D and other related compounds is attributed to the free acid form of the chemicals (Munro et al 1992) and may be mediated by effects associated with the plasma membrane, interference in cellular metabolic pathways involving acetyl coenzyme A, or uncoupling of oxidative phosphorylation (Bradberry et al 2000). Their herbicide action is mediated through plant hormone pathways, but to the best of our knowledge no solid evidence has been presented to date to support endocrine-like activity of these compounds in mammals or other species.…”
Section: Discussionmentioning
confidence: 99%
“…brushing on health because of the high number of exhaust gases and the multiple potential interactions Munro et al (1992) concluded that cohort studies of (BAPE 1997). exposed workers do not generally support the specific hypothesis that 2,4-D causes any form of cancer.…”
Section: Worker Health Aerial or Ground Application (Glyphosate) Manumentioning
confidence: 99%
“…The influence of dosedependent 2,4-D toxicokinetics (TK) as an important determinant for expression of toxicity has also been characterized in multiple species, including humans. 2,4-D has been the subject of several epidemiological studies and comprehensive reviews as well as multiple studies to characterize potential human and environmental exposure levels (reviewed in Munro et al 1992;USDA 1998;Garabrant & Philbert 2002;US EPA 2005;Bus & Hammond 2007;Aylward et al 2010;Burns & Swaen 2012).…”
Section: Introductionmentioning
confidence: 99%